High-SNR Staining Algorithm for One-Way Wave Equation-Based Modelling and Imaging (Communications in Computational Physics, 2020)
Staining algorithms based on two-way wave equation migration methodshave been applied to improve the signal-to-noise ratio (SNR) of poorly illuminatedstructures such as those in subsalt zones. In regular staining algorithms, when a sourcewavefield reaches the stained area that is associated with the target structures, a newwavefield called stained wavefield is excited, and this stained wavefield forward extrapolates synchronously with the real source wavefield. The forward-extrapolatedstained and real source wavefields are cross-correlated with the backward-extrapolatedreceiver wavefield, and we obtain the stained and the real reverse time migration(RTM) images. The staining algorithms for RTM can suppress the noise of non-targetregions and obtain high SNR images of the target structures. Whereas RTM methodsare limited by the low computational efficiency and SNR, by contrast, one-way waveequation migration (OWEM) methods have the advantages of high efficiency and nointerference from multiples. Thus, we developed a new staining method based on thegeneralised screen propagator (GSP) as a case of OWEM methods for subsalt imaging.Furthermore, a new stained wavefield called stained receiver wavefield is proposedhere, forming two new staining strategies for seismic imaging, in which forward-propagated source and backward-propagated receiver wavefields can be convenientlyselected to be stained at the stained area. Numerical experiments demonstrated thatthis staining GSP method is more effective in improving the SNR of subsalt structurescompared to conventional GSP migration and RTM methods; moreover, these newstaining strategies as applied to the OWEM methods can greatly improve the SNR ofweakly illuminated structures in subsalt zones, in comparison with regular stainingalgorithms for one-way methods.